2015
DOI: 10.1210/en.2015-1315
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Abundance in Zebrafish Embryos Is Regulated by Complementary Actions of the Endocannabinoid System and Retinoic Acid Pathway

Abstract: The endocannabinoid system (ECS) and retinoic acid (RA) signaling have been associated with influencing lipid metabolism. We hypothesized that modulation of these pathways could modify lipid abundance in developing vertebrates and that these pathways could have a combinatorial effect on lipid levels. Zebrafish embryos were exposed to chemical treatments altering the activity of the ECS and RA pathway. Embryos were stained with the neutral lipid dye Oil-Red-O (ORO) and underwent whole-mount in situ hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 65 publications
(58 reference statements)
3
27
0
Order By: Relevance
“…Increasing endocannabinoid (ECS) activity by treatment with 0.3 mM WIN, as we previously demonstrated, caused an increase in ORO staining and expansion of the stained areas (Fraher et al, 2015). While decreasing ECS activity with 3 mM Rimo decreased the area and intensity of ORO staining in the body of the embryos (Fraher et al, 2015) (Fig. 3A, n = 10 embryos per treatment).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Increasing endocannabinoid (ECS) activity by treatment with 0.3 mM WIN, as we previously demonstrated, caused an increase in ORO staining and expansion of the stained areas (Fraher et al, 2015). While decreasing ECS activity with 3 mM Rimo decreased the area and intensity of ORO staining in the body of the embryos (Fraher et al, 2015) (Fig. 3A, n = 10 embryos per treatment).…”
Section: Resultssupporting
confidence: 65%
“…We developed this method using wild-type (WT) zebrafish during early embryogenesis. We tested this method using two known pharmacological compounds targeting the cannabinoid pathway that were previously shown to modify lipid content during zebrafish embryogenesis (Fraher et al, 2015) Rimonabant (Rimo), a CB1 selective inverse agonist and WIN 55,212-2 mesylate (WIN) a pan CB receptor agonist. The quantification method that was developed was approached having three aims in mind:…”
Section: Introductionmentioning
confidence: 99%
“…A role for the cannabinoid receptor CB1 in obesity and energy homeostasis has been established in relation to food intake and energy balance (25,26). Activation of the CB1 receptor centrally and peripherally leads to altered energy balance and weight gain in model organisms (19,(27)(28)(29). Selective blockade of CB1 with rimonabant in human clinical trials demonstrated an effect on weight loss (30,31), but further evaluation of cardiovascular outcomes was limited by psychiatric side effects, including an apparent increase in suicide risk (32).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AEA administration to zebrafish has been shown to increase expression of Srebp, a transcription factor involved in sterol synthesis (Migliarini & Carnevali 2008). In another study, Fraher et al showed that alteration of the activity of the eCBs and Retinoic Acid (RA) pathways have additive function in lipid abundance during zebrafish development (zebrafish embryos were exposed to chemical treatments WIN55212-2, Rimonabant, 4-diethylaminobenzaldehyde, BMS 753, BMS 614, BMS 961, CD 2665, oleamide, AM 630, bisphenol A diglycidyl ether, and Rosiglitazone) (Fraher et al 2015).…”
Section: The Ecbs In Zebrafishmentioning
confidence: 99%
“…showed that alteration of the activity of the eCBs and Retinoic Acid (RA) pathways have additive function in lipid abundance during zebrafish development (zebrafish embryos were exposed to chemical treatments WIN55212‐2, Rimonabant, 4‐diethylaminobenzaldehyde, BMS 753, BMS 614, BMS 961, CD 2665, oleamide, AM 630, bisphenol A diglycidyl ether, and Rosiglitazone) (Fraher et al . ).…”
Section: Introductionmentioning
confidence: 97%